Continued nintedanib in patients with systemic sclerosis-associated interstitial lung disease: 3-year data from SENSCIS-ON - Yannick Allanore; Dinesh Khanna; Oliver Distler; Maureen D Mayes; Madelon C Vonk; Kristin B Highland; Arata Azuma; Veronika Kohlbrenner; Margarida Alves; Alexandra James (RMD Open)
Objective We assessed adverse events and changes in forced vital capacity (FVC) in patients treated with open-label nintedanib over 148 weeks of SENSCIS-ON, the extension of the SENSCIS trial.Methods Adverse events and changes in FVC over 148 weeks of SENSCIS-ON were assessed in patients who received nintedanib in SENSCIS and continued nintedanib in SENSCIS-ON (‘continued nintedanib’ group) and in patients who received placebo in SENSCIS or received nintedanib for ≤28 days in a drug–drug interaction study and then received nintedanib in SENSCIS-ON (‘initiated nintedanib’ group).Results The continued nintedanib group comprised 197 patients, and the initiated nintedanib group comprised 247 patients (231 from SENSCIS). Diarrhoea was the most frequent adverse event, reported in 152 (77.2%) and 183 (74.1%) patients in the continued nintedanib and initiated nintedanib groups, respectively. Among patients in the continued and initiated nintedanib groups, respectively, 53 (26.9%) and 148 (59.9%) had ≥1 dose reduction, 72 (36.5%) and 131 (53.0%) had ≥1 treatment interruption and 29 (14.7%) and 72 (29.1%) had adverse events that led to treatment discontinuation. Mean (SE) changes in FVC (mL) at week 148 were −189.1 (29.5) in the continued nintedanib group and −126.4 (26.4) in the initiated nintedanib group.Conclusion The safety profile of nintedanib over 148 weeks of SENSCIS-ON was consistent with that reported in SENSCIS. Changes in FVC during SENSCIS and SENSCIS-ON supported a continued effect of nintedanib on slowing the decline in lung function, but showed continued progression of SSc-ILD.